Solid block to assembly block conversion on a welding - Marbun, Abri Andry Saresa; Purba, Adi Syahputra; Ramadhan, M. Noviriandi; Andaresta, Windy; Cahyagi, Danang (International Journal of Mechanical Computational and Manufacturing Research, 2025)
Block damage often occurs due to the pressing process and the presence of residual welding dirt on the slug so that a repair process is needed by means of grinding. If there is damage to the solid block, repairs are carried out on all sides of the block so that this is less effective and efficient in repair time. This research was conducted by changing the design of solid blocks into assembly blocks which aims to make the process of repairing blocks effective and efficient. To find out the results of the differences between solid blocks and assembly blocks, a trial was carried out by calculating the repair process time using a grinding machine with a depth of 0.04 mm. The results of the solid block repair process trials obtained an average of 397 seconds while the assembly blocks obtained an average of 248 seconds. Thus cutting the repair process time by 149 seconds. With this design change, the effectiveness and efficiency of block repair time is obtained.